Hubungan antara Ekspresi Emosi Keluarga Pasien dengan Kekambuhan Penderita Skizofrenia di RS Dr. Sardjito Yogyakarta - Carla R Marchira, Sumarni P., Lusia P.W (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Schizophrenia is considered as severe mental disorder which causes big burden in one’s life. After being hospitalized, schizophrenic patients will live with their family while do regular visitation to the hospital to get medical treatment under doctor’s supervision. Schizophrenic patient’s care often becomes a burden for the family, either financially, physically, and emotionally. Studies showed that many families have high expressed emotion due to high relapse rate on schizophrenic patient. Sex difference also affects course and schizophrenic prognosis. There are still limited data about these issues available in the field of mental health.Objective: To observe correlation between families expressed emotion and relapse rate of schizophrenia patients at Dr. Sardjito Hospital. We observed drug compliance and activity daily living of schizophrenia patients as well.Method: This study used cross sectional design. Subjects were schizophrenic patients who were being treated at Dr Sardjito Hospital and their families. The sample size was 31. Instruments used in this study were: Expressed emotion instrument by Soekarto (2001), Compliance Scale by Widiyanto (2002), and ADL instrument. Data were analyzed with Chi-Square and Pearson Correlation test. We performed linear regression test to determine the contribution of expressed emotion towards patient’s relapse rate.Result : Data collection showed that 61.3% schizophrenic patient’s families had high expressed emotion, meanwhile 74.2% schizophrenic patients were relapse. Chi-Square test showed significant correlation between patient family’s expressed emotion and schizophrenic patients relapse rate(X2=8,22; p<0,05). Pearson Correlation test also showed positive correlation between patient family’s expressed emotion and schizophrenic patients’ relapse rate (C=0,59). We found the r2=24,2%.Conclusion: There is a significant correlation between patient’s family expressed emotion with patient’s relapse rate. High expressed emotion of the family has contribution on increasing schizophrenic patients’ relapse rate.Keywords : expressed emotion, relapse, schizophrenia, drug compliance, ADL